Two narrowly endemic new species of Siphocampylus (Campanulaceae) from Santa Catarina, southern Brazil - Funez, Luís Adriano; Hassemer, Gustavo (Phytotaxa, 2016)
This contribution presents and describes Siphocampylus baccae and S. sevegnaniae, two narrowly endemic new species from waterfalls and rocky cliffs in Santa Catarina state, southern Brazil. We assess the conservation status of both species as critically endangered (CR) according to the IUCN criteria. We present descriptions, photographs, a distribution map and taxonomic comments on the new species along with an identification key to the species of Siphocampylus that occur in Santa Catarina.